We're not the champions - West, Tracey, 1965- (West, Tracey, 1965- Underdogs (Series), 2022)
Duke's cousin Coco, an elegant French bulldog from Paris, is coming to Barksdale Academy as an exchange student, and Duke is worried about what she will think about his often uncouth friends, the Underdogs; Coco joins Team Awesome for the K-2 exam where the Barksdale teams compete against a rival school, but it turns out that Coco has problems with the athletic events, and it is up to the Underdogs to rescue their school's reputation.